Measurement of the Omega0c and Xi0c baryon lifetimes using hadronic b-baryon decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2025)
The lifetimes of the $$ {\varOmega}_c^0 $$and $$ {\Xi}_c^0 $$baryons are measured using a pp collision dataset collected by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1. The charm baryons are produced in the fully reconstructed decay chains $$ {\varOmega}_b^{-}\to {\varOmega}_c^0\left(\to p{K}^{-}{K}^{-}{\pi}^{+}\right){\pi}^{-} $$and $$ {\Xi}_b^{-}\to {\Xi}_c^0\left(\to p{K}^{-}{K}^{-}{\pi}^{+}\right){\pi}^{-} $$. The measurement uses topologically and kinematically similar B− → D0(→ K−K+π−π+)π− decays for normalisation. The measured lifetimes areτΩc0=276.3±19.4stat±1.8syst±0.7τD0fs,τΞc0=149.2±2.5stat±0.9syst±0.4τD0fs,$$ {\displaystyle \begin{array}{c}{\tau}_{\varOmega_c^0}=276.3\pm 19.4\left(\textrm{stat}\right)\pm 1.8\left(\textrm{syst}\right)\pm 0.7\left({\tau}_{D^0}\right)\textrm{fs},\\ {}{\tau}_{\Xi_c^0}=149.2\pm 2.5\left(\textrm{stat}\right)\pm 0.9\left(\textrm{syst}\right)\pm 0.4\ \left({\tau}_{D^0}\right)\textrm{fs},\end{array}} $$ where the first uncertainty is statistical, the second systematic and the third due to the uncertainty of the D0 lifetime. These results are consistent with previous measurements performed by the LHCb experiment.